Adolescent Worry Induction: An Experimental Laboratory Evaluation. Issue 1 (March 2014) - Frala, Jamie; Mischel, Emily; Knapp, Ashley; Autry, Kevin; Leen-Feldner, Ellen
Available research indicates that worry is an important process in need of further investigation, particularly among adolescents. While a sizable body of literature has examined the nature, prevalence, and correlates of worry in both adults and youth, laboratory investigations of this variable using a real-time worry induction paradigm have been completed almost exclusively with adults. The current study aimed to extend the literature by experimentally examining the validity of a worry induction in a sample of adolescents. Fifty adolescents between the ages of 12 and 17 years were randomly assigned to either a worry or a neutral thought condition. Results provided initial support for the validity of using an ideographic worry induction procedure with adolescents, suggesting the induction produces elevated generalized negative affectivity and future-oriented mentation relative to a control group. Unexpectedly, predictions regarding the effects of the induction on verbal-linguistic thoughts were not supported. Results are discussed in terms of their convergence and divergence with the adult literature as well as relevant developmental factors to consider in future utilization of worry induction procedures in order to better understand the phenomenology and consequences of worry among youth.